KEPENTINGAN AUSTRALIA DALAM PERJANJIAN MARITIM DENGAN REPUBLIK DEMOKRATIK TIMOR LESTE TAHUN 2018 - Mutia Hairani; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research analyses Australia’s decision to accept the maritime agreement with Timor-Leste in 2018. Before the agreement took place, Australia and Timor-Leste did not have a permanent maritime boundary separating them in the Timor Sea because of the different principles in determining how maritime boundaries are drawn. Australia wanted the maritime boundaries to be drawn based on the principle of the natural prolongation of the continental shelf, while Timor-Leste wanted maritime boundaries to be drawn using the median line between the two countries. In 2016, Timor-Leste submitted a compulsory non-binding conciliation to resolve maritime boundary dispute to Permanent Court of Arbitration (PCA). In this compulsory non-binding conciliation process to define maritime boundaries between them, Australia had then agreed to define maritime boundaries drawn based on the median lines. Australia’s acceptance the agreement on its maritime boundaries with Timor-Leste certainly raises a question on the interests behind its decision.This research uses the neorealism perspective that focuses on the implications of the anarchic feature of the international system to state’s policy. Using foreign policy theory with rational actor model approach, this research aims to describe Australia’s strategy and approach to achieve its national interest and resolve maritime disputes with Timor-Leste. The data in this research was collected through literature study.This research shows that Australia’s decision to accept the agreement to settle the maritime dispute has been driven by the economic factors; the industrialization of oil and gas from the Timor Sea is still taking place in Australia. Australia has several interests in this agreement. First, the economic benefits for Australia. Second, support for the economic development of Timor-Leste. Third, Australia’s consistency in promoting the peaceful settlement of maritime disputes based on international law. Keywords: Maritime Boundary Dispute, Australia, Timor-Leste, Timor Sea, Timor Gap, Maritime Boundary, UNCLOS, Foreign Policy.